The Measurement and Determinants of Bank's Performance in Malaysia - Zuraida, Nasir (2012)
We analyzed the performance of domestic banks operating in Malaysia for the period of 7 years, from 2005 to 2011. In this study, we used financial ratios of banks by extracting components of CAMELS Model, namely, Capital adequacy, Asset quality, Management Quality, Earnings, Liquidity and Sensitivity to Market Risk. To identify the determinants of performance of the Malaysian domestic banks during 2005-2011 years, this study has chosen multiple regression analysis. The descriptive analysis suggested that the average ROA for the Malaysian commercial banks during the study period was closed to 1%(0.99%).The results show that bank performance (measured by ROA) of commercial banks in Malaysia was influenced by the Capital Adequacy ratio, Asset Quality ratio,Management Quality ratio, NIM, Liquidity ratio and Sensitivity to Market Risk ratio. Overall,CAMELS predicts 60.6% of ROA. The significant determinants of ROA among CAMELS measurement over the study period were Management Quality, Liquidity and Sensitivity to Market Risk.